Conservation in Context: Toward a Systems Framing of Decentralized Governance and Public Participation in Wildlife Management. Issue 2 (12th December 2018) - Sullivan, Leeann
Abstract: Governance scholars have long championed the adaptive utility of decentralized management institutions, in part due to their ability to bring diverse stakeholders into decision‐making processes. However, research into the link between decentralization and participation often looks at policy design but bypasses important system feedbacks that shape sustained participation over time. To paint a more robust picture detailing how decentralization and participation are related, this paper uses a complex systems framework to explore interacting structural, operational, and cultural components of decentralized wildlife governance institutions in the United States and Botswana. Through this comparative analysis, I argue that the landscape of public participation in decentralized governance institutions appears to be significantly impacted by three factors: 1) how decentralization processes occurred, 2) where in the process of decision making participation is situated, and 3) perceptions of power distribution between groups with competing interests. 环境保护：建立一个公众参与野生动物管理的分权治理制度框架: 研究治理的学者长期以来一直支持分权管理机构的适应性应用，部分原因在于它们有能力让各种利益相关者参与决策过程。然而，关于分权与参与之间联系的研究往往着眼于政策设计，而忽略了影响长期持续参与的重要系统反馈。为了更有力地描述分权和参与之间的关系，本文运用复杂的系统框架来探索美国和博茨瓦纳野生动物分权治理机构的相互作用结构、运作和文化组成部分。通过这一比较分析，笔者认为分权治理机构中的公众参与情况似乎受三大因素的显著影响：1) 权力下放是如何实现的；2) 在决策过程中，参与扮演哪种角色; 3) 利益冲突群体间权力分配的认知。 Conservación en contexto: hacia un marco de sistemas de gobierno descentralizado y participación pública en el manejo de la vida silvestre: Los académicos de gobernanza han defendido durante mucho tiempo la utilidad adaptativa de las instituciones de gestión descentralizadas, en parte debido a su capacidad para incorporar a diversos interesados ​​a los procesos de toma de decisiones. Sin embargo, la investigación sobre el vínculo entre descentralización y participación a menudo analiza el diseño de políticas, pero pasa por alto importantes comentarios del sistema que dan forma a la participación sostenida en el tiempo. Para dibujar una imagen más sólida que detalle cómo se relacionan la descentralización y la participación, este documento utiliza un marco de sistemas complejos para explorar los componentes estructurales, operativos y culturales de las instituciones descentralizadas de gobernanza de la vida silvestre en los Estados Unidos y Botsuana. A través de este análisis comparativo, sostengo que el panorama de la participación pública en las instituciones de gobierno descentralizado parece verse significativamente afectado por tres factores: 1) cómo se produjeron los procesos de descentralización; 2) donde se sitúa en el proceso de toma de decisiones la participación; y 3) percepciones de la distribución de poder entre grupos con intereses en competencia.